Clinical practice guidelines for the treatment of Covid-19 in Brazil: A systematic review - Lanes, Taís Carpes; Ribeiro , Mariane Albuquerque Lima; Oliveira, Daianny Seoni de; Junior, Marcos Gabriel do Nascimento; Garcia, Filipe Reis; Melo, Jéssyca Maria França de Oliveira; Tiguman, Gustavo Magno Baldin (Revista Cuidarte, 2021)
Introduction: Coronavirus disease (Covid-19) is an infectious disease affecting the respiratory tract, which emerged in China and spread rapidly throughout the world. Objective: To evaluate the methodological quality and transparency of Brazilian clinical practice guidelines for the treatment of coronavirus disease (Covid-19). Materials and Methods: A systematic review was conducted in 2020 on Medline (via PubMed), Embase, Scopus, LILACS, National Guideline Clearinghouse and Guidelines International Network databases, in addition to online searches on the Brazilian Ministry of Health, Brazilian Medical Association, Federal Council of Medicine, Federal Council of Nursing and Federal Council of Physical Therapy websites. The methodological quality and transparency of the guidelines were assessed using the second version of the Appraisal of Guidelines for Research and Evaluation (AGREE) instrument developed by four authors. Results: 33 guidelines were found of which 14 were included in the analysis. There was only one guideline that scored above 60% in all domains. Among the six domains, higher scores were found in the following three domains: scope and objective, stakeholder involvement and clarity of presentation. Discussion: Despite methodological weakness found, the authors were keen to provide clear and concise recommendations through key information and therapeutic options to facilitate decision making. Conclusions: Brazilian clinical practice guidelines were found to be of poor methodological quality, from which only one guideline was recommended and classified as to be of high methodological quality and transparency.How to cite this article: Lanes, Taís Carpes; Ribeiro, Mariane Albuquerque Lima; Oliveira, Daianny Seoni de; Junior, Marcos Gabriel do Nascimento; Garcia, Filipe Reis; Melo, Jéssyca Maria França de Oliveira; Tiguman, Gustavo Magno Baldin. Diretrizes de prática clínica para o tratamento da Covid-19 no Brasil: uma revisão sistemática. Revista Cuidarte. 2021;12(2):e2025 http://dx.doi.org/10.15649/cuidarte.2025
Keywords: Coronavirus Infections; Pandemics; Systematic Review; Guidelines as Topic; Therapeutics